Hyponatremia of children of two months to five years of age with community-acquired pneumonia and its correlation with severity of illness and its outcome. - Roy, Arnab; Majumdar, Rahul; Mahajan, Divya; Chatterjee, Mridula (Indian Journal of Child Health, 2025)
Background: Pneumonia is an acute respiratory infection of the lungs where alveoli become inflamed and are filled with pus and fluid, leading to impaired oxygen exchange, respiratory distress, and painful breathing. Community-acquired pneumonia (CAP) remains the leading single cause of mortality in the pediatric age group worldwide. This study aims to study hyponatremia in community-acquired pneumonia among children of 2 months to 5 years of age and its correlation with severity of illness, course, outcome and length of stay in hospital. Material and Methods: This was a prospective observational study conducted in the pediatric inpatient ward & pediatric intensive care unit (PICU) of North Bengal Medical College. The study was conducted from July 2023 to December 2024 with a duration of 18 months. Children admitted to the pediatric inpatient ward or PICU with a clinical diagnosis of CAP according to the WHO criteria were included in the present study. Results and Conclusion: The present study highlights that hyponatremia is a common finding in children with CAP. This study also highlights the significant association of hyponatremia with severe pneumonia, the association of severe hyponatremia with severe pneumonia, increased need for ventilation, prolonged hospital stays, and higher mortality in children with CAP.